2016
DOI: 10.1371/journal.pntd.0005019
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Zika Virus Isolate from Colombia

Abstract: BackgroundZika virus (Flavivirus genus) is the first mosquito-borne virus known to cause high rates of microcephaly and abortion in humans. Typically, Zika virus causes a self-limiting, systemic illness; however, the current outbreak of Zika virus in the Americas has been associated with increased rates of fetal malformations and Guillain-Barré syndrome. Very few Zika virus isolates have been described in the literature, and live viruses are needed to perform studies of pathogenesis and to develop vaccines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…Viral RNA was extracted from cell supernatants harvested from DENV infected HEK-293T cells using QIAamp Viral RNA Mini Kit as per manufacturer instructions (Qiagen). Eluted RNA samples were subjected to qRT-PCR with very speci c primers and probe of DENV-2 capsid region and TaqMan fast virus one step master mix (Applied Biosystems) as described previously 33 . Estimation of viral RNA (copies/mL) was carried out by using the standard curve generated from DENV-2 transcripts.…”
Section: Methodsmentioning
confidence: 99%
“…Viral RNA was extracted from cell supernatants harvested from DENV infected HEK-293T cells using QIAamp Viral RNA Mini Kit as per manufacturer instructions (Qiagen). Eluted RNA samples were subjected to qRT-PCR with very speci c primers and probe of DENV-2 capsid region and TaqMan fast virus one step master mix (Applied Biosystems) as described previously 33 . Estimation of viral RNA (copies/mL) was carried out by using the standard curve generated from DENV-2 transcripts.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that 8, 000 μW/cm 2 of UV light could destroy hepatitis B virus while 330, 000 μW/cm2 destroyed the fungus Aspergillus niger. Most virus become inactivated by UV light at dose of 200, 000 μW/cm 2 [79] while Zika virus may have higher resistance to UV light [79]. Therefore, UV light could be a viable solution to reducing contamination rates in non-sterile LN 2 .…”
Section: Contamination Controlmentioning
confidence: 99%
“…Though this assembler is not designed primarily as a metagenomic assembler, the authors assert that it is capable of performing well with samples of uneven coverage, a problem encountered when assembling environmental or heterogeneous samples. The software has been used in the assembly of viruses such as Zika virus and H1N1 influenza [37,38]. Following a similar strategy, PRICE [30] also builds out an assembly using greedy paired end extension.…”
Section: Overlap Based Assemblersmentioning
confidence: 99%